Development of Authentic Assessment Instruments to Measure Students' Critical Thinking Skills in Science Learning on Temperature and Heat (Case Study of Grade XI Students of SMAN 2 Medan) - Lioni Widya Sonata Tampubolon; Yeni Megalina (Pustaka Digital Indonesia, 2025)
This research is urgent due to the need for an assessment instrument that measures students’ critical thinking rather than memorization, supporting contextual evaluations aligned with the Merdeka Curriculum. This study aims to develop an authentic assessment instrument in the form of cause and effect multiple choice questions that can measure students' critical thinking skills in the subject of temperature and heat. This study is a research and development. The study uses the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data collection techniques used in this study included expert validation sheets to assess content validity, student response questionnaires to measure practicality, and test instruments administered to 11th grade students at SMA Negeri 2 Medan to evaluate empirical validity and reliability. The data analysis techniques consisted of Aiken’s V analysis to determine the validity of the items based on expert judgment, reliability testing using Cronbach’s. The validation results showed that the instrument was highly valid based on the Aiken index. Of the 50 questions developed, 36 were declared feasible and valid. The reliability test showed a value of 0.946, which is classified as very high. The difficulty level of the questions ranged from 0.30 to 0.71, with 3 questions classified as difficult, 29 as moderate, and 4 as easy. The discriminating power of the questions ranged from 0.20 to 0.70, with 10 questions in the good category, 23 questions in the fair category, and 3 questions in the poor category. The effectiveness of the distractors showed that 35 questions were very good and 1 question was fair. These results indicate that the authentic assessment instrument developed is suitable for measuring students' critical thinking skills and can assist teachers in conducting more comprehensive and contextual learning evaluations.